2021
DOI: 10.3390/biomedicines9111719
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Flavonoids Icaritin and Icariin Protect against Cerebral Ischemia–Reperfusion-Associated Apoptosis and Extracellular Matrix Accumulation in an Ischemic Stroke Mouse Model

Abstract: Stroke, which is the second leading cause of mortality in the world, is urgently needed to explore the medical strategies for ischemic stroke treatment. Both icariin (ICA) and icaritin (ICT) are the major active flavonoids extracted from Herba epimedii that have been regarded as the neuroprotective agents in disease models. In this study, we aimed to investigate and compare the neuroprotective effects of ICA and ICT in a middle cerebral artery occlusion (MCAO) mouse model. Male ICR mice were pretreated with bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…It has been shown previously that some flavonoid extracts from food or herbal sources have a potential mutagenic effect linked to the concentration of flavones. Therefore, it is of utmost importance to thoroughly study the side effects of flavonoids before declaring them safe for supplemental use [ 98 ]. The toxicological profile associated with various flavonoids preparations in the market remains an area of limited research, as most of these flavonoid preparations available as herbal medicines or dietary supplements, with different claimed therapeutic effects, have yet to undergo rigorous controlled clinical trials to establish their efficacy [ 96 ].…”
Section: Toxic Effects Of Flavonoidsmentioning
confidence: 99%
“…It has been shown previously that some flavonoid extracts from food or herbal sources have a potential mutagenic effect linked to the concentration of flavones. Therefore, it is of utmost importance to thoroughly study the side effects of flavonoids before declaring them safe for supplemental use [ 98 ]. The toxicological profile associated with various flavonoids preparations in the market remains an area of limited research, as most of these flavonoid preparations available as herbal medicines or dietary supplements, with different claimed therapeutic effects, have yet to undergo rigorous controlled clinical trials to establish their efficacy [ 96 ].…”
Section: Toxic Effects Of Flavonoidsmentioning
confidence: 99%
“…National Natural Science Youth Fund Project (82001270); National Natural Science regional foundation project (82160242); Basic research project of Guizhou science and technology plan (qiankehe foundation ZK [2021] General 413); Doctoral research start-up fund (gyfybsky-2021-23). The Health Commission of Guizhou Province (gzwjkj 2020-1-015).…”
Section: Data Availability Statementmentioning
confidence: 99%
“…Icariin, which is a type of flavonoid, is the main ingredient that is extracted from Epimedium ( Jin et al, 2019 ). Multiple pharmacological activities, such as antioxidant, anti-inflammatory, and antiapoptotic activities, have been attributed to Icariin, which may account for the compound’s purported preventative and therapeutic efficacy in conditions as diverse as ischaemic stroke ( Liu et al, 2018 ; Dai et al, 2021 ; Wu et al, 2021 ), AD ( Ma et al, 2021 ; Wang et al, 2022 ; Yan et al, 2023 ), Parkinson’s disease ( Lu et al, 2018 ; Zeng et al, 2019 ; Khezri and Ghasemnejad-Berenji, 2022 ), multiple sclerosis ( Shen et al, 2015 ; Cong et al, 2020 ), and depressive disorder ( Cao et al, 2019 ; Xu et al, 2020 ; Zeng et al, 2022 ). Several studies have demonstrated that Icariin treatment can suppress Aβ production to improve learning and memory in animals ( Jin et al, 2014a ; Chen et al, 2016a ; Chuang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…It may prevent oxidative injury to neurons, reduce brain inflammation, and promote neuroplasticity. These effects may be beneficial for AD, PD [ 34 ], MS, Schizophrenia [ 36 ], and Ischemic Stroke [ 37 , 38 ]. Due to its neuroprotective, anti-inflammatory, and antioxidant properties, icariin can be utilized as a neuroprotective treatment for ALS.…”
Section: Introductionmentioning
confidence: 99%